A Space Fractional Uphill Dispersion in Traffic Flow Model with Solutions by the Trial Equation Method - Rfaat Moner Soliby, Rfaat Moner Soliby; Jamaian, Siti Suhana (mdpi, 2023)
This paper has two main objectives. First, we modify the traffic flow model by introducing the uphill dispersion that derives from the fact that, in peak hours, drivers tend to travel from low to high density regions. This means that the proposed model recovers wrong-way travel and is free from advected discontinuity. Second, in order to describe the anomalous transport behavior, we fractalize the proposed model to include dynamics with the fractional in space. As a result of adopting the fractional Fick’s law, several moving jam waves are presented which elucidate the nonhomogeneity of driving styles. Then, the GFFD fractional derivative and the trail equation method are applied and for some special cases solutions are simulated which could help transportation engineers to understand traffic behavior and thus make appropriate decisions when constructing a traffic signals network.